(NoSNOWY MIKROBIOLOGII I WIRUSOLOGII (B:s (Nu^EBNOE POSOBIE DLQ BIOLOGI^ESKIH SPECIALXNOSTEJ UNIWERSITETOW (B/s - (N~URIKOWA(B, (NwIKTORIQ wIKTOROWNAs; (NwIKTOROW(B, (NdMITRIJ pETROWI^s ((NwORONEV (B:s (NiZD(B-(NWO wORONEV(B. (NUN(B-(NTA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 266s
(NpREDM(B. (NUKAZ(B.: (NS(B. 267-270s
Keywords: (NwIRUSOLOGIQs; (NmIKROBIOLOGIQs